Instrumental Student Cognitive Conflict in Solving Mathematical Problems - Ratnah Lestary; Ahbi Mahdianing Rum (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
This research was a case study research with a qualitative approach. The subject of this study was 6 class VIII students of SMPN 1 Kota Malang. The instruments of this study were cognitive quest conflict test sheets, general interview instructions, validation sheets, and record tools. The data obtained in the form of the results of the subject's work, interview data on the subject, and field notes. The results of this study indicated that cognitive conflict of students with instrumental understanding in solving comparison problems occurs when: (1) students determine the formula matching the problem and (2) students do algorithmic calculations. Student cognitive conflict when determining the appropriate comparison formula was the awareness of the contradiction between the answers obtained from applying a comparison formula worth the concept of a reverse value comparison. Student cognitive conflict when performing algorithmic calculations were (a) awareness that the initial scheme is to simplify the comparison of the number of people, tables and days was incorrect because it cannot be applied to solve all problems of comparison and (b) awareness that the calculation scheme was looking for multiplication patterns the known comparison cannot be applied because it produces an answer that was not an integer